Membrane technology : in the chemical industry - Pereira Nunes, Suzana, ....-; Peinemann, Klaus-Viktor, ....- (Weinheim : Wiley, 2006)
Pt. I. Membrane materials and membrane preparation. 1. Introduction. 2. Membrane market. 3. Membrane preparation. 4. Presently available membranes for liquid separation. 5. Surface modification of membranes. 6. Membranes for fuel cells. 7. Gas separation with membranes. Pt. II. Current application and perspectives. 1. The separation of organic vapors from gas streams by means of membranes. 2. Gas-separation membrane applications. 3. State-of-the-art of pervaporation processes in the chemical industry. 4. Organic solvent nanofiltration. 5. Industrial membrane reactors. 6. Electromembrane processes. 7. Membrane technology in the chemical industry : future directions.